Psalm 44: "Why do you hide your face, 0 God?!" - Human, Dirk J. (Verbum et ecclesia, 1998)
Since the appearance of Hermann Gunkel's form critical categories, Psalm 44 has mostly been identified by scholars as the first Communal lament of the Psalter. This genre classification has, since then, been refined, but didn't change the view on this Volkskiage much. Modern research on the psalm can mainly be confined to the issues of the structure, the historical setting (Sitz im Leben) and theology of the poem. On the structure and historical setting of Psalm 44, a variety of interpretation possibilities are offered. The exegete's imagination, though, is captured by the enigmatic theological problem posed by the text. This problem reflects the tension between faith in God on the one hand and the reality of life on the other, where the faithful believer is often afflicted, humiliated or injured. Then he experiences God's absence or hiddenness, despite his own faithfulness to Him. The literary feature of contrast seems to play a significant role in Psalm 44. In the text strategy of this artistic composed poem, this feature is revealed in the psalm's language and structure, in order to display the secret and mysterious image and activity of God. This article attempts to illustrate how this literary feature contributes to the understanding of the theological problem experienced by the psalmist.